Training on Improving Entrepreneurial Skills for Students of the Faculty of Economics and Business, Malikussaleh University - Jannah, Miftahul; agustinar; Rianti. S, Nova; Agustinawati; Ramazalena, Rauzi; Habibi, Muhammad; Syahyudi, Ilham (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2024)
Abstract: The